Dimensión política del discurso del director de comunicaciones en el escenario corporativo (2003)
The political dimension in the discourse of communication directors on the corporate scene is a part of the research the discourse of the corporate communicator; and it is the result of an interpretation work of the data administered by the communicators of the twelve organizations that constitute the sample. Likewise, the title suggests a rectification which turns out to be indispensable and which has to do with the limits and reaches of the research, since the actors are, in their great majority, directors in the area of communication.This essay aims at delving into the thesis proposed through the text: “The constitution of the Individual in the Discourse of the Corporate Communicator”, in which the political feature is sustained in the constitution of his identity as a strategist, as well as in the action he unfolds with the publics (internal and external) for the achievement of the organization’s purposes.Now then, if in the aforementioned thesis, the emphasis was made on the building of the identity; in this case, the analysis is centered into the linguistic statements with which actions, purposes and strategic functions are expressed, which in turn acquire a political feature, as long as the strategist’s position responds to the function of an ally which the organization confers to him. In his condition of an ally, the Communicator will have to harmonize the exercising of a power which is only exercised by those who really boast of it; and hence, he will put his know-how to the service of the institution, a fact which, in the sphere of communication management, is translated into the ability for the symbolic control of the publics with whom the organization is related.The aforementioned allows us to. argue that, although the communicator’s political aspiration is the positioning of the communication area in the domain of the organization’s high spheres which, in turn represents the acquisition of a prestige for him, the power that he reaches lies within his ability for: congregating wills, orientating the individuals actions, and positioning the organization in the business sphere; That is why it may be affirmed that the strategist communicator’s political action fulfills the role of an absorber or an “earth pole” of the power effects exercised by those who boast of it; and thus, his political purpose is to diminish such effects and to achieve the adhesion of the social actors (publics) to the interests of the institution. Nonetheless, such an action, far from being plain, acquires attention modalities in variances related to the administration’s style, as well as to that of the communicator. For the effects of sustaining the political dimension of the corporate communicator’s discourse y, subsequently, the modalities his action adopts, the text presents the following structure: firstly, it is about contextualizing and delimiting the notion of politics, as well as its relation to power. Secondly, it analyzes, from the discourse perspective, a corpus of enunciations emitted by the communicators throughout the interview, having in mind the categories of: the action front, political reference, strategic function, and political purposes. Thirdly, an approximations is to the modalities of the communicator’s political action, parting from the identification of common constants or features. Finally, the contingent feature of the political action is approached, under the supposition that such contingency is determined essentially by three variances: nature of the organization, managerial style, and the communicator’s modality of administration.